Highly Efficient Vanadium-Catalyzed Transformation of CH4 and CO to Acetic Acid - Taniguchi, Yuki; Hayashida, Taizo; Shibasaki, Hiroyasu; Piao, Dongguo; Kitamura, Tsugio; Yamaji, Teizo; Fujiwara, Yuzo (Organic letters, 1999)
The VO(acac)2 (acac = 2,4-pentanedionato) catalyst in the presence of K2S2O8 and CF3COOH has been found to efficiently transform methane and CO to acetic acid selectively. The reaction of methane (5 atm) with CO (20 atm) at 80 °C for 20 h gives acetic acid in 93% yield based on methane. Other vanadium compounds such as V2O3, V2O5, and NaVO3 and various vanadium-containing heteropolyacids such as H5PV2Mo10O40, H4PVW11O40, and H5SiVW11O40 also work as catalysts.